COMPARACIÓN DE ALGUNAS DE LAS TÉCNICAS DE PREDICCIÓN EN ANÁLISIS DE SERIES TEMPORALES - Ospina Martínez, Raydonal; Zamprogno, Bartolomeu (Revista Colombiana de Estadística, 2003)
In this work, we compared the forecasting performance of three approaches: Box & Jenkins, exponential smoothing and neural networks, under different forecasting horizons. Two series are considered